NGO Involvement in the Indonesia-EFTA CEPA Negotiations on Palm Oil - Giffary Salsha Al Fajrin; Shanti Darmastuti; Dairatul Ma'arif (Jurnal Hubungan Internasional, 2023)
Crude palm oil is considered a strategic export commodity for Indonesia because of its contribution to the domestic economy and development so the government will always ensure that agreements related to CPO are included in the discussion of international trade agreements, including the IndonesiaEFTA CEPA. However, the agreement related to CPO in Indonesia-EFTA CEPA received an unfavorable response from several national NGOs in Switzerland who are members of The Swiss Palm Oil Coalition. They urged the government of Switzerland to exclude CPO from the free trade agreement. This research aimed to find out the involvement of NGO in Indonesia-EFTA negotiations on palm oil using the conceptual framework of economic diplomacy. The research method used in this paper is descriptive qualitative. The data collection methods used are interview methods, document-based methods, and internet-based methods with data analysis techniques consisting of data reduction, data presentation, and verification and conclusion drawing. Based on the results of the research, it can be concluded that the form of NGO involvement in the palm oil negotiations in the Indonesia-EFTA CEPA can be divided into two, namely NGOs as consulting partners, and NGOs as pressure groups. Keywords: Crude Palm Oil; Economic Diplomacy; Indonesia-EFTA CEPA; NGO